A physical education : how I escaped diet culture and gained the power of lifting - Johnston, Casey (Grand Central Publishing, 2025)
"A Physical Education traces Casey Johnston's journey of calorie restriction and obsessive cardio-making herself small in almost every way-to finding healing through the (unexpected) practice of lifting weights. As she progresses, carrying groceries and closing heavy doors become easier. As she diligently practices checking in with how she feels, she begins to question not only how she has treated her body, but how she sees herself and the world. This growth also fuels a deeper understanding: how the mainstream messaging she received about women's bodies has seeped into almost every other area of her life. Combining wit, rage, and a reporter's eye for detail, Johnston recounts how she learned the process of rupture, rest, and repair-not just within her cells and muscles, but within her spirit. A love letter to the science of female strength, this is a book for anyone who's ever longed to return home to their own body"-- Provided by publisher.